2001
DOI: 10.1103/physrevb.64.033409
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant effect in heteroepitaxial growth: The Pb-Co/Cu(111) case

Abstract: A MonteCarlo simulations study has been performed in order to study the effect of Pb as surfactant on the initial growth stage of Co/Cu(111). The main characteristics of Co growing over Cu(111) face, i.e. the decorated double layer steps, the multiple layer islands and the pools of vacancies, disappear with the pre-evaporation of a Pb monolayer. Through MC simulations, a full picture of these complex processes is obtained. Co quickly diffuses through the Pb monolayer exchanging place with Cu atoms at the subst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…It has been demonstrated in the literature that by using surfactants, the problem of asymmetric interfaces can be reduced to a large extent [16][17][18][19][20][21][22]. The prerequisites for a material to qualify as a surfactant is its optimal quantity and a low as compared to other elements present in the multilayer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in the literature that by using surfactants, the problem of asymmetric interfaces can be reduced to a large extent [16][17][18][19][20][21][22]. The prerequisites for a material to qualify as a surfactant is its optimal quantity and a low as compared to other elements present in the multilayer.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies [23][24][25][26][27] have also demonstrated the beneficial effect of Pb as surfactant in evaporated and MBE-grown FM/NM multilayers. Several other surfactant elements such as Bi, [26][27][28][29][30] Ag, [31][32][33][34][35] Au 36 and In 37 have been similarly found to induce layer quality improvement for physically deposited multilayers.…”
Section: D332mentioning
confidence: 99%
“…Recently, a few models were proposed to describe the growth behavior in SME. [13][14][15][16][17][18] For instance, Wu et al constructed a reactionlimited aggregation ͑RLA͒ model 14 which includes the following atomistic processes: diffusion of adatoms on the surfactant terrace and exchange of adatoms with their underneath surfactant atoms for nucleation ͑seed exchange͒ or for becoming incorporated at the existing island edges ͑aided exchange͒. Using kinetic Monte Carlo ͑KMC͒ simulations, the model reproduces the fractal-to-compact island shape transition as observed experimentally in Ge growth on Pb-covered Si͑111͒.…”
Section: Introductionmentioning
confidence: 99%